Examination of specific DNA by PCR in patients with different forms of Lyme borreliosis - Pícha, Dušan; Moravcová, Lenka; Holečková, Daniela; Žďárský, Emanuel; Valešová, Marie; Marešová, Vilma; Třešňák Hercogová, Jana; Vanousová, Daniela (International journal of dermatology, 2008)
BACKGROUND: Borrelial specific DNA was examined in a group of 62 patients with different forms of Lyme borreliosis (LB) (32 patients suffered from neuroborreliosis, 19 manifested erythema migrans, and 11 joint involvement). METHODS: Nested-PCR system with five newly derived primers was used in parallel. The study was organized prospectively, the presence of DNA was tested for plasma, CSF, joint fluid and urine before treatment, and plasma, joint fluid and urine were examined after treatment. RESULTS: Before therapy, 36 patients (58.1%) were DNA positive on the whole; 21 positive patients (65.6%) were found in the group of neuroborreliosis, 8 (42.1%) showed signs of skin involvement, and 7 (63.6%) were positive in arthritis. After treatment, 11 patients (36.7%) were positive in neuroborreliosis, 3 (17.6%) in skin form, and 6 (54.5%) in joint form of LB. Among 97 positive amplifications the most frequent target was found in primer corresponding with 16S rDNA (50 samples, 51.5%). Lower but very similar results were obtained with primers for OspA (18 positive amplifications; 18.6%), OspC (13 positive amplifications; 13.4%), and flagellin (13 positive amplifications; 13.4%). There were 11 patients in whom only DNA and no specific antibodies were found. CONCLUSIONS: Specific DNA was found in all clinical groups of LB with similar sensitivity. Examination of the borrelial DNA in urine displayed the same sensitivity as in CSF and had a two times higher sensitivity than in plasma.
Keywords: protilátky bakteriální; lymeská nemoc; polymerázová řetězová reakce; Polymerase Chain Reaction; DNA bakterií; DNA, Bacterial; lidé; Borrelia burgdorferi komplex; Sensitivity and Specificity; kůže; DNA primery; senzitivita a specificita; Antibodies, Bacterial; Borrelia burgdorferi Group; infekční artritida; prospektivní studie; Prospective Studies; Skin; Lyme Disease; DNA Primers; Arthritis, Infectious; Humans